(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Anaplastic thyroid carcinoma (ATC) is an aggressive and rare form of thyroid cancer, representing 1-2% of thyroid malignancies but accounting for the majority of thyroid cancer-related deaths due to its rapid progression, invasiveness, and resistance to standard therapies. This report highlights the case of a 60-year-old male histopathologically diagnosed with ATC stage IV as there were lymph node metastases. The patient was managed with a multidisciplinary team approach and had total thyroidectomy followed by systemic chemotherapy and three-dimensional conformal radiotherapy. The reported case highlights the importance of aggressive, integrated therapeutic approaches in managing ATC, emphasizing personalized, multidisciplinary care, advanced radiotherapy techniques, and molecular-targeted therapies for improved outcomes. Bangladesh J. Nuclear Med. 28(1): 164-169, 2025